MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA MADRASAH ALIYAH ALHUDA GORONTALO PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN DENGAN PENDEKATAN PROBLEM POSING (Suatu Penelitian di Kelas XI IPA MA Al-Huda Gorontalo TP 2008/2009) - ., Masrina; Lukum, Astin; Sihaloho, Mangara (Jurnal Entropi, 2009)
This research is class act based research that had been done on the second semester 2008/2009 academic year, the total number of students are fifteen (15), consist of four (4) men and elevent (11) women. This research is done into two cycles and use one teacher as observer 1 and one else observer 2. the aim of the research is to increase the students learning result of class XI IPA MA Al-Huda Gorontalo on solubility and solubility product by using problem possing approach. In this research, the dat are taken by teacher activities monitoring sheet and students as long as teaching and learning process, also the test of students learning result. The succsessfull qualification of this research is 85% students get mark 6,5 also monitoring to teacher activities and students achieve 70%. From the result of research show that learning by using problem possing approach can increase the students learning result. It can be proven on increasing the students learning result 20% in cycle I, from 73,3% to 93,3%or average the mark from 64,3 to 71,2.